Does Eryngium maritimum seeds extract protect against CCl4 and cisplatin induced toxicity in rats: Preliminary phytochemical screening and assessment of its in vitro and in vivo antioxidant activity and antifibrotic effect. (October 2017) - Mejri, Houda; Tir, Meriam; Feriani, Anouar; Ghazouani, Lakhdhar; Salah Allagui, Mohamed; Saidani-Tounsi, Moufida
Highlights: Methanol extract of Eryngium maritimum seeds. Phytochemical screening. Hepatoprotective and nephroprotective effect. Abstract: The present work was undertaken to investigate the protective effects of Eryngium maritimum seeds extract (MEE) against CCl4 and cisplatin induced toxicity in rats. The levels of total phenolics and flavonoids were ca. 20 mg GAE/g and ca. 19 mg QE/g, respectively. Using HPLC twenty-one molecules were identified. MEE showed important in vitro antioxidant activities. Results demonstrated that MEE-treatment restored the increased activities of AST, ALT, LDH and ALP and the high levels of serum creatinine, urea and uric acid levels induced by CCl4 and cisplatin treatment. Moreover, MEE presented important in vivo antioxidant activities; increased the activities of CAT, SOD and GPx and decreased the TBARS and protein carbonyl contents. The histopathological studies suggested that MEE clearly alleviated the degree of tissues fibrosis. The obtained results highlighted the potential use of E. maritimum as a source of bioactive compounds with hepatoprotective and nephroprotective advantages.